The effect of seawater based media on copper dissolution from low-grade copper ore. (February 2015) - Torres, C.M.; Taboada, M.E.; Graber, T.A.; Herreros, O.O.; Ghorbani, Y.; Watling, H.R.
Highlights: Seawater based media affect copper dissolution from low-grade copper ore. Presence of the Cl − ions causes the formation of chloro-copper complexes. Use of seawater in mining processes has advantages in the northern part of Chile. Abstract: Due to the scarcity of water in the north of Chile, there is interest in small-scale mining using seawater to leach the minerals. This situation has led to this research aimed to determine the effect of different process variables on the extraction of copper based on the ore type of these small-scale mining activities. The extraction of copper from finely ground (<150 μm) low-grade mixed ore (0.36% Cu) was studied in different acidic media (H2 SO4 and HCl). The effects of water quality (tap water, seawater and synthetic process water) and lixiviants on copper leaching were investigated at three temperatures (25 °C, 35 °C and 45 °C). Synthetic process water was prepared by adding Na +, Cl −, Cu 2+ and SO4 2− to seawater. Copper extractions between 70% and 80% were achieved in 48 h using seawater, similar to the extractions obtained using tap water. Rapid copper dissolution occurred when synthetic process water was used, from 90% to 97%. This marked increase was related to the addition of Cu 2+, which promoted the formation of CuCl + . Seawater was comparable to freshwater in terms of leaching kinetics and yield potential by raising the chloride concentration and increasing the formation of copper chloride ions. The findings of this study also expanded our understanding of the consequences of substituting seawater for freshwater at industrial leaching operations.